H2S-Donating trisulfide linkers confer unexpected biological behaviour to poly(ethylene glycol)–cholesteryl conjugates. Issue 17 (30th March 2020) - Ercole, Francesca; Li, Yuhuan; Whittaker, Michael R.; Davis, Thomas P.; Quinn, John F.
Abstract : A comprehensive in vitro study into trisulfide-bearing PEG-conjugates was conducted. For these materials the combination of a cholesteryl group and an H2 S donating moiety is required to confer cytoprotective and ROS-mitigating effects. Abstract : Inspired by the properties of the naturally occurring H2 S donor, diallyl trisulfide (DATS, extracted from garlic), the biological behaviour of trisulfide-bearing PEG-conjugates was explored. Specifically, three conjugates comprising an mPEG tail and a cholesteryl head were investigated: conjugates bridged by a trisulfide linker (T ), a disulfide linker (D ) or a carbamate linker (C ), and a fourth comprising two mPEG tails bridged by a trisulfide linker (P ). H2 S testing using both a fluorescent chemical probe in HEK293 cells and an amperometric sensor to monitor release in suspended cells, demonstrated the ability of the trisulfide conjugates, T and P, to release H2 S in the presence of cellular thiols. Cytotoxicity and cyto-protective capacity on HEK293 cells showed that T was the best tolerated of the conjugates studied, and remarkably more so than D or C . Moreover, it was noted that application of T conferred a protective effect to the cells, effectively abolishing the toxicity associated with co-administered C . The interaction of conjugates and combinations thereof with the cell membrane of HEK cells, as well as ROS generation were also investigated. It was found that C caused significant membrane perturbation, correlating with high losses in cell viability and pronounced generation of ROS, especially in the mitochondria. T, however, did not disturb the membrane and was able to mitigate the generation of ROS, especially in the mitochondria. The interplay of the cholesteryl group and H2 S donation for conferring cytoprotective effects was clearly demonstrated as P did not display the same beneficial characteristics as T .